The dialectization of psychic life: Sartre and his dialectical conception of the lived (vécu) - Fujiwara, Gustavo (Argumentos - Revista de Filosofia, 2023)
The present article traces the dialectical way in which Sartre, since the 1960s, acclimates yhe psychic life and the lived. For this purpose, we will conduct an investigative incursion supported by a set of Sartrean writings from this period, with special focus on the essay Questions of method (1957) and the conference that our author gave in 1961, which the title, Marxism and subjectivity, reveals his attempt to reconcile existentialism and historical materialism in the light of an existential dialectic. Subsequently, we show how the dialectic of psychic life, which presupposes a dialectical antinomy (presence to the self and absence of the self), gives rise, on the part of the philosopher, to a specific criticism of Freudian psychoanalysis.